IMPLEMENTASI KEBIJAKAN PELAYANAN PUBLIK BERBASIS ELEKTRONIK DI KABUPATEN SERDANG BEDAGAI (STUDI KASUS PELAYANAN AKTA KELAHIRAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL) - Elsaria Damanik; Marlan Hutahaean; Artha Tobing (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Electronic-based public services are a government innovation aimed at improving service quality to be faster, more efficient, transparent, and easily accessible. The Department of Population and Civil Registration of Serdang Bedagai Regency has implemented this system in birth certificate services. This study aims to analyze the implementation of the policy and the factors influencing it. This research uses a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques.The results show that the implementation of electronic-based public service policies has generally run quite well and has improved service efficiency. Based on George C. Edwards III’s theory, the success of implementation is influenced by communication, resources, disposition, and bureaucratic structure. However, there are still obstacles such as limited infrastructure and low digital literacy among the community. In conclusion, the implementation of this policy is fairly effective, but improvements are needed in socialization, human resource capacity, and access to technology to optimize public services.